Lean management and low carbon emissions in precast concrete factories in Singapore - Wu, Peng; Low, S. (2012)
Many studies have investigated the benefits that can be achieved through the use of the lean production philosophy to meet the challenges of sustainable development. These benefits include reduced waste, lead time, inventory, and improved efficiency. Because of the rising recognition of global climate change, this paper aims to identify the contribution of the lean production philosophy to environmental sustainability in precast-concrete factories, using CO 2 emissions as the indicator. This study adopts a weighted-factor model comprising 17 precasters in the Singapore precast-concrete industry. Two stages in the production cycle are investigated using the weighted-factor model: site layout management and delivery management. The results indicate that there are many non-value-adding activities in the precast-concrete production process that contribute to an increase in the level of carbon emissions. Large storage area, large quantity supply base, lack of just-in-time (JIT) sourcing with the suppliers, and a lean workforce appear to be the most important non-value-adding activities in site layout management and delivery management. The analysis provides good-practice guidance and can be used as a checklist for precasters to identify the non-value-adding activities in the precast-concrete production process to achieve low-carbon production. The results will also be useful for regulatory agencies to provide recommendations for the precast-concrete industry to reduce carbon emissions. © 2012 American Society of Civil Engineers.